TOURISM SAFETY AND PRODUCTIVITY: ROLE OF INTELLIGENCE - Nurmukhammad Oppokkhonov (European Journal of Life Safety and Stability (2660-9630), 2021)
This paper represents the impact of intelligence on tourism safety and tourist revisit intentions. Our findings reflect the evidence that human intelligence rate, measured by nation-IQ, is positively related with tourism safety. This article includes that, on average moving from a country with the lowest IQ score (61) to the one with highest (107.1) is associated with an increase in the rate of tourism safety. The link between intelligence and tourism safety remains robust when we account for the feedback from environment to intelligence. We empirically, investigate the interactive effect of tourism safety and intelligence on tourism productivity.